Two new balsams (Balsaminaceae) from Eastern Himalayas, India - Hareesh, Vadakkoot Sankaran; Sabu, Mamiyil (Phytotaxa, 2020)
Two new balsams (Impatiens), I. tirbinensis and I. shiyomiensis are described from Arunachal Pradesh, India. Species shows affinities towards I. drepanophora and I. rugosipetala but distinct in many attributes. Detailed descriptions, distribution, ecology and colour photographs of the new species are provided along with the comparison of I. drepanophora.